2020
DOI: 10.1088/2053-1591/ab6534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological properties of composite made of marble dust-reinforced C93200 copper alloy

Abstract: Composite materials are unique because reveal great physical, mechanical and thermal properties. However, there is yet huge potential to enhance their features by adding specific reinforcement in the matrix in order to reach the requirements of a particular application. This paper presents detailed research on the impact of marble dust reinforcement to mechanical and tribological features of copper based metal alloy (C93200 series) composites dedicated for bearing applications. The novel composites made with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The improved corrosion resistance can be attributed to the MD particles' uniform distribution and effective barrier properties, which inhibit corrosive agents' penetration into the composite matrix. MD particles act as a corrosion inhibitor, protecting the ADC 12 matrix from corrosive attack [59].…”
Section: Effect Of MD On Corrosion Behavior Of Adc 12 Compositementioning
confidence: 99%
“…The improved corrosion resistance can be attributed to the MD particles' uniform distribution and effective barrier properties, which inhibit corrosive agents' penetration into the composite matrix. MD particles act as a corrosion inhibitor, protecting the ADC 12 matrix from corrosive attack [59].…”
Section: Effect Of MD On Corrosion Behavior Of Adc 12 Compositementioning
confidence: 99%
“…On the other hand, while investigating the normal load influence on specific wear rate, the lowest wear rate was observed for the composite with 2.5 wt % of marble dust. Marble dust (1.5–6 wt %) reinforced copper alloy was also used by Rajak et al [ 127 ]. The authors observed that all composites were characterized by lower wear loss against different sliding velocities compared to copper alloy without reinforcement.…”
Section: Industrial Waste Materialsmentioning
confidence: 99%
“…The worn surface micrographs revealed that 4.5 wt% addition of MD filler exhibit superior wear resistance (showing small grooves) in comparison to unreinforced copper alloy that shows ploughing signs. 30 The prime reason for such an occurrence is the better bonding between the base matrix and hard reinforcement particles thus producing minimum wear loss. 45 Sharma et al determined the influence of MD reinforcement and heat treatment on friction and wear properties of Al6063 alloy composites.…”
Section: Effect Of Marble Dust On Tribological Propertiesmentioning
confidence: 99%
“…The worn surface micrographs revealed that 4.5 wt% addition of MD filler exhibit superior wear resistance (showing small grooves) in comparison to unreinforced copper alloy that shows ploughing signs. 30…”
Section: Tribological Characterization Of Materials Using Industrial Wastesmentioning
confidence: 99%